FRI0410 Rheumatoid arthritis (RA) care: Geographic disparities and impact of primary care physicians on access to rheumatologists. (23rd January 2014) - Widdifield, J.; Bernatsky, S.; Paterson, J.M.; Thorne, J.C.; Tu, K.; Bombardier, C.
Abstract : Background: Earlier population-based assessments have demonstrated that many Canadians are not provided optimal RA therapy. 1 This is especially true for seniors with RA. Little is known about potential barriers that limit access to rheumatologists for patients with new-onset RA. In the province of Ontario, all 13 million residents are covered by universal public health insurance. However, access to specialists depends on referral at the primary-care level and not all patients have a regular primary care physician. Primary care physicians play an essential role in ensuring that RA patients receive optimal care, since prompt referral to a rheumatologist is required to confirm a diagnosis and initiate prompt treatment. Objectives: To estimate the percent of incident RA patients who encounter rheumatologists within 1 year of diagnosis, and to identify determinants of contact with a rheumatologist within 1 year of RA diagnosis. Methods: We assembled an incident RA cohort aged ≥66 years from Ontario health administrative data across 1997-2008. We used a standard algorithm to identify 27, 127 seniors with new onset RA 1 . We followed patients for 1 year, assessing if they had a visit to a rheumatologist. We assessed secular trends and differences for patients who had received rheumatology care (defined as ≥1 rheumatology encounter) versus those who had not. We performed multilevel logistic regression analysesto determine whether receipt of rheumatology care was associated with patient demographics, clinical factors, primary care physician characteristics, provider continuity, and geographic characteristics (rheumatology supply, distance to a rheumatologist). Results: Overall, 17830 (66%) seniors with new-onset RA identified over 1997-2008 received rheumatology care within 1 year of diagnosis. This increased from 50% in 1997 to 78% in 2008. The majority of patients (67%) were women, and the mean (±SD) age at cohort entry was 74.6 (±6.01) years. Few patients (16%) resided in rural areas. Factors associated with a rheumatologist encounter included having a regular primary care physician [adjusted Odds Ratio (OR)=1.30 95% CI 1.11, 1.53], and having more rheumatologists in the area (Rheumatology supply per 100 000 adults OR=1.20 95% CI 1.16, 1.24). Less contact with rheumatologists occurred among patients who were older (OR=0.97 95% CI 0.97, 0.98), had a male primary care physician (OR=0.73 95% CI 0.66, 0.80), resided in rural areas (OR=0.74 95% CI 0.68, 0.81) and at a remote distance (≥100 km) to the closest rheumatologist (OR=0.37 95% CI 0.31, 0.44). Conclusions: Improvements in access to rheumatologists for RA care have occurred over time but more efforts are needed. Measures of poor access (rural, remote, absence of a regular primary care physician) negatively impacted rates of encounters with a rheumatologist. The lower contact with rheumatologists for residents of rural and remote areas suggests problems with access that may ultimately affect quality of care for patients with RA. References: Widdifield J, et al. Arthritis Care Res 2011;63:53-7. Disclosure of Interest: None Declared